2009
DOI: 10.1016/j.esas.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biologic effects of spine implant debris: Fact from fiction

Abstract: BackgroundBiologic-reactivity to implant-debris is the primary determinant of long-term clinical performance. The following reviews: 1) the physical aspects of spinal-implant debris and 2) the local and systemic biologic responses to implant debris.MethodsMethods included are: 1) gravimetric wear analysis; 2) SEM and LALLS; 3) metal-ion analysis; 4) ELISA, toxicity testing, patch testing; and 5) metal-lymphocyte transformation testing (metal-LTT).ResultsWear and corrosion of spine-implants produce particles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 186 publications
2
72
0
Order By: Relevance
“…Reportedly, spinal implant debris elicits a macrophage-mediated response with increased levels of local pro-inflammatory cytokines, osteoclastogenesis and cellular apoptosis [8,13,29,40]. The results of this in vivo study support this and this response is both dose dependent and can persist over the long term.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Reportedly, spinal implant debris elicits a macrophage-mediated response with increased levels of local pro-inflammatory cytokines, osteoclastogenesis and cellular apoptosis [8,13,29,40]. The results of this in vivo study support this and this response is both dose dependent and can persist over the long term.…”
Section: Discussionsupporting
confidence: 75%
“…Metal-on-metal total disc arthroplasties and fusion implants have been shown to produce wear debris particles in both the micron and submicron sizes [13,18,27,32,35]. Recent retrieval analysis of metal-on-metal total disc arthroplasty debris by Guyer et al [12] has reported the CoCr-alloy implant debris to be primarily in the submicron range.…”
Section: Introductionmentioning
confidence: 99%
“…Further muddying the waters, especially in studying failed TDRs, is that many of the failures have a mechanical component, component subsidence or loosening, that might itself be the cause of pain. Similarly, previous case studies [3] in humans and experiments using animal models have demonstrated that the pain is more likely due to the inflammation that is part of the biologic reaction to debris and not a neuropathic effect.…”
Section: Corr Insightsmentioning
confidence: 99%
“…Still, reports of osteolysis and adverse local tissue reactions (ALTRs) similar to those seen around hip and knee replacements have emerged [3], substantiating the continuing concern that the biological reaction to debris may be an important factor limiting the longevity of disc replacements. Veruva and colleagues have provided additional compelling evidence that these concerns are warranted, and have begun to explore the hypothesis that a link exists between the presence of debris in local tissues and evidence of biological responses consistent with increased pain.…”
mentioning
confidence: 99%
“…The main concern in using these metal-based hip replacements is the formation of wear debris 2) and ion elution, 3) which seem to be closely related to the microstructure and precipitates of the CoCrMo alloy implants. It is well known that the phase, morphology, size and distribution of the precipitates affect the properties of CoCr Mo alloys.…”
Section: Introductionmentioning
confidence: 99%